KCNC1‐related disorders: new de novo variants expand the phenotypic spectrum. Issue 7 (7th June 2019) - Park, Joohyun; Koko, Mahmoud; Hedrich, Ulrike B. S.; Hermann, Andreas; Cremer, Kirsten; Haberlandt, Edda; Grimmel, Mona; Alhaddad, Bader; Beck‐Woedl, Stefanie; Harrer, Merle; Karall, Daniela; Kingelhoefer, Lisa; et al.
Abstract: A recurrent de novo missense variant in KCNC1, encoding a voltage‐gated potassium channel expressed in inhibitory neurons, causes progressive myoclonus epilepsy and ataxia, and a nonsense variant is associated with intellectual disability. We identified three new de novo missense variants in KCNC1 in five unrelated individuals causing different phenotypes featuring either isolated nonprogressive myoclonus (p.Cys208Tyr), intellectual disability (p.Thr399Met), or epilepsy with myoclonic, absence and generalized tonic‐clonic seizures, ataxia, and developmental delay (p.Ala421Val, three patients). Functional analyses demonstrated no measurable currents for all identified variants and dominant‐negative effects for p.Thr399Met and p.Ala421Val predicting neuronal disinhibition as the underlying disease mechanism.